Thermodynamic reassessment of the Ag–Cu phase diagram at nano-scale. (March 2021) - Chu, M.Z.; Qin, Y.Z.; Xiao, T.; Shen, W.; Su, T.; Hu, C.H.; Tang, Chengying
Abstract: The Ag–Cu phase diagram at nanoscale was reassessed by CALculation of PHAse Diagrams (CALPHAD) method, considering the surface effect on the chemical potential of pure substance and excess Gibbs free energy of mixtures. According to the reported thermodynamic properties of pure Ag and Cu nanoparticles (NPs), and the measured melting eutectic temperatures of Ag8 Cu2, Ag7 Cu3, Ag6 Cu5 to Ag5 Cu5 NPs, respectively, obtained in the previous works, self-consistent thermodynamic parameters including the size effect were obtained by thermodynamic optimization. Using the obtained thermodynamic parameters, four Ag–Cu nano phase diagrams were constructed, and thermodynamic properties were calculated. It was indicated that the calculated Ag–Cu nano phase diagrams agreed well with experimental data. Highlights: The phase diagrams of Ag–Cu nanoalloys were thermodynamically re-investigated. A self-consistent thermodynamic data set including the size effect was obtained. Four Ag–Cu nano phase diagrams were constructed and compared with experimental data. The calculated Ag–Cu nano phase diagrams agreed well with experimental data.